Integrasi Layanan Peminjaman Sarana Prasarana dalam Manajemen Aset Menggunakan Framework Codeigniter dan Boostrap - Sarimuddin, Sarimuddin; Nasarudin, Nasarudin; Pasrun, Yuwanda Purnamasari; Ningsi, Nurfitria; Sudarman, La (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Campus assets are a means of supporting performance to support attracting interest and supporting student teaching and learning activities. The assets of an organization must be well managed so that they can operate effectively and efficiently so that they can deliver high benefits. So far, the asset management system at USN Kolaka Campus B still uses Microsoft Excel to manage assets for asset data collection and special notebooks for borrowing assets, which creates difficulties when controlling assets that are easily moved (means) such as infocus, printers, chairs and others. The use of this facility requires asset tracking and good supervision if a facility is in poor condition or even damaged, so a system is needed that can carry out asset management as well as provide asset lending services. This system uses the CodeIgniter and Boostrap framework so that the use of program code is simple, safe and responsive to various screen sizes. The performance of this system controls assets when the asset location is moved, whether through borrowing, permanent transfer, or a change in physical condition (good or damaged). This can be used as a reference by the Asset Technical Implementer (UPT) so that asset management can run effectively and efficiently. The measure of system feasibility was calculated using a Likert scale obtained from the results in questionnaire with 12 respondents. The calculations are carried out taking into account 3 aspects, namely information quality, system quality and service quality. The measurement results of the three aspects are of a usability value of 87%, so the system that was built obtains the title of very feasible.